Religion and public administration: the unacknowledged common (and competitive) ground - Cunningham, Robert (2005)
Traditional public administration is a function of governance. Tasks should be carried out effectively, and in a way that enhances the sense of community. For social services, meeting the demands of both body and spirit are important. Toward the end of the twentieth century the demands for efficiency, lowest cost provider, and separation of church and state curtailed the public administrator's ability to meet other than needs of the body. Contracting out, often through faith based organizations, challenges public administrators to meet client's needs of the spirit. -Reproduced.
Keywords: Religion; Public administration